She persisted in sports : American Olympians who changed the game - Clinton, Chelsea; Boiger, Alexandra (New York : Philomel Books, 2020)
"Stories of American woman Olympians who persisted and succeeded against the odds" --
Keywords: Women athletes -- History; Women Olympic athletes -- United States -- Biography; Olympics -- History; Sports for women -- History; Women Olympic athletes -- History -- Juvenile literature; Women Olympic athletes -- United States -- Biography -- Juvenile literature; Olympics -- History -- Juvenile literature; Sports for women -- History -- Juvenile literature; Biographies -- Juvenile